Effects of habitat quality on parasite abundance: do forest fragmentation and food availability affect helminth infection in the Eurasian red squirrel?. (4th February 2015) - Santicchia, F.; Romeo, C.; Martinoli, A.; Lanfranchi, P.; Wauters, L. A.; Ferrari, N.
Abstract Habitat quality affects demography, population genetics, space use and phenotypic characteristics of mammals. However, little is known about the effects of habitat quality, fragmentation and/or food abundance, on host–parasite interactions. Here we present a first study on the relationships between the abundance of the dominant gastrointestinal helminth, Trypanoxyuris (Rodentoxyuris) sciuri, infecting the Eurasian red squirrel Sciurus vulgaris and three environmental factors: habitat type (mountain conifer forests vs. lowland mixed deciduous forests), fragmentation (fragmented woodlands vs. continuous forests) and food availability. Abundance of T. (R.) sciuri increased in fragmented woods. Furthermore, in mountain conifer forests, squirrels were more heavily infected after a poor Norway spruce seed crop than in years with medium or high seed production, indicating that squirrels are less capable of reducing parasite load when food availability is low. Hence, we suggest that T. (R.) sciuri abundance in red squirrels may be determined mainly by changes in host susceptibility induced by higher stress levels and/or poorer nutritional status, while in fragments, reduced genetic diversity may also increase host susceptibility to parasite infection. Although our data do not shed light on the mechanisms generating the observed patterns, results from other field studies highlighted the effect of stress and nutritional status on parasite infection, thus suggesting their implication in the changes in the abundance of T. (R.) sciuri.